A Right to Vote: A Case Study in Nursing Advocacy for Public Policy Reform - Abram Oudshoorn (York University Libraries, 2019)
In February 2014, the Government of Canada under Stephen Harper introduced the 'Fair Elections Act'. This reform to the elections act removed provisions for access to voting for individuals lacking certain forms of identification. Noting that this would have a disproportionate impact on people experiencing homelessness, nursing advocates joined with other activists to try to prevent then subsequently overturn this legislation. The purpose of this paper is to explore the 93rd competency of the College of Nurses of Ontario, "Advocates and promotes healthy public policy and social justice," by unpacking a case example of advocacy for voting rights. This paper addresses the challenges faced by nurses in doing public policy advocacy and concludes with lessons learned. Fulfilling our college mandated requirement to be politically active means ensuring that public policies are just, equitable, and reflective of the progressive values of Nursing.